Nuclear or cytoplasmic expression of survivin: What is the significance? - Li, Fengzhi (2005)
Growing evidence suggests that survivin expression in cancer cell nuclei may represent an important prognostic marker to predict disease outcome for cancer patients. Current reports in this research area, however, are inconsistent and propose opposing conclusions regarding the significance and prognostic value of survivin nuclear expression. The aim of our study is to review and discuss the data reported in the original publications. We have also provided new experimental data to support our view regarding the possible reasons for the observed inconsistencies in the literature. This would alert researchers to pay attention to potential pitfalls in the determination of nuclear or cytoplasmic expression of survivin for the future.